Pengaruh Kualitas Produk dan Motivasi Konsumen terhadap Keputusan Pembelian pada Produk Sepatu Sandal Eiger - Moch. Virgiawan Anjasmara; Nuruni Ika K.W (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to analyze product quality and consumer motivation towards purchasing decisions on Indonesian eiger sandals. Research methodology: This study uses quantitative research methods that are processed using Smart PLS software. To determine the sample in this study using a non-probability sampling method with the technique used is incidental sampling with a total sample of 85 samples. The results showed that product quality and consumer motivation had a positive and significant effect on purchasing decisions on the Eiger sandal shoe product. The limitation of this research is that it only uses one object of research and has not used several companies with different backgrounds. The results of this study can be useful for marketing in the company's consistency process in the next period as an effort to increase the purchase of eiger sandals. Keywords: produk quality; consumer motivation;buying decision